Strengthening women’s voice and agency in Nigeria: Evidence from a randomized control trial on women’s advocacy and men’s allyship trainings - Adida, Claire; Kosec, Katrina; Kyle, Jordan; Mo, Cecilia H.; Arriola, Leonardo; Adeyanju, Dolapo; Fisher, Rachel (International Food Policy Research Institute, 2024)
This policy brief presents insights from a randomized controlled trial (RCT) conducted across three states of southwestern Nigeria (Oyo, Ogun, and Osun), examining the effectiveness of advocacy and leadership training for women, along with allyship training for men (their husbands), in improving women’s voice and agency in community governance. With over 5,800 women participants across 450 communities, this study tested whether training women alone, as well as whether training them in tandem (though in separate sessions) with their husbands, can increase women’s political participation in local governance or the responsiveness of local leaders to women’s priorities. We show causal improvements in both when women are trained and chart out emerging policy lessons.